Assessment of Clinical Profile of Patients with Nasal Septal Deviations - Srilatha K (Asian Journal of Medical Research, 2021)
Background: The aim is to assess clinical profile of patients with nasal septal deviations. Subjects and Methods: Ninety- four patients of deviated nasal septum of both genders were recruited for the study. Nasal patency test was done followed by anterior rhinoscopy. NOSE questionnaire was applied consisted of 0 being the lowest and 4 being the highest. Deviations were classified according to Mladina classification. Results: Out of 94 patients, there were 54 males and 40 females. Septal deformities according to Mladina classification was type I seen in 4, type II in 8, type III in 6, type IV in 14, type V in 36, type VI in 20 and type VII in 6 cases. Grading was caudal in 46, mid-septum in 30 and posterior septum in 18. Symptoms were nasal discharge in 82, nasal obstruction in 42, headache in 16, facial pain in 25, epistaxis in 11 and hyposmia in 28. The difference was significant (P< 0.05). The mean pre- operatively NOSE value was 58.4 and post- operatively was 30.2. The difference was significant (P< 0.05). Conclusion: Deviated nasal septum is common among people. Common symptoms were nasal obstruction, headache, facial pain, and nasal discharge. Septoplasty resulted in significant improvement in NOSE score.